Food security, competitiveness erosion, and the illusion of sustainability: insights from Romania’s pig sector - Istudor, Nicolae; Ignat, Raluca; Petrescu, Irina-Elena; Constantin, Marius; Deaconu, Elena-Mădălina; Teodor, Cristian (Transformations In Business & Economics, 2026)
The pig sector is confronting numerous challenges under the European Union’s (EU) stricter socio-economic and environmental sustainability requirements, which complicate the management of African Swine Fever (ASF) and its market effects. Farmers face increasing difficulty in remaining both environmentally compliant and economically efficient. In this context, some EU countries face declining pig meat production capacity and growing reliance on pig meat imports to satisfy domestic demand. Among EU member states, Romania is among the most affected, as reflected by the size of its pig meat trade deficit, which represents the country’s largest deficit among agri-food products. The objective of this research was to provide market insights capable of serving as a foundation for policy measures designed to improve the performance of the Romanian pig sector. This paper proposes an integrative descriptive framework to jointly examine food security, competitiveness, and environmental impacts in the Romanian pig sector over the 2011–2022 period. Data were drawn from the Romanian National Institute of Statistics, the International Trade Centre, and FAOSTAT. The results indicate that Romania's dependence on pig meat imports is associated with weaker domestic production potential in the context of ASF management, with implications for the sector's structural sustainability. Food security risks therefore emerge, in addition to the food safety concerns arising from the intensification of ASF. By contrast, Romania’s domestic pig-livestock emissions remain low within the EU, but this apparent sustainability gain largely reflects production contraction and import dependence.
Keywords: pig meat sector; food security; trade balance deficit; import dependency; environmental externalisation; Romania